2011
DOI: 10.1124/jpet.110.178715
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-Induced Desensitization/Resensitization of Human G Protein-Coupled Receptor 17: A Functional Cross-Talk between Purinergic and Cysteinyl-Leukotriene Ligands

Abstract: G protein-coupled receptor (GPR) 17 is a P2Y-like receptor that responds to both uracil nucleotides (as UDP-glucose) and cysteinyl-leukotrienes (cysLTs, as LTD 4 ). By bioinformatic analysis, two distinct binding sites have been hypothesized to be present on GPR17, but little is known on their putative cross-regulation and on GPR17 desensitization/resensitization upon agonist exposure. In this study, we investigated in GPR17-expressing 1321N1 cells the cross-regulation between purinergic-and cysLT-mediated res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 34 publications
4
39
0
Order By: Relevance
“…Although multiple follow-up studies consistent with this original report have been published by the same group (Parravicini et al, 2008;Pugliese et al, 2009;Buccioni et al, 2011;Daniele et al, 2011;Coppi et al, 2013), Benned-Jensen and Rosenkilde (2010) reported that UDP and UDP-glucose, but not cysteinyl leukotrienes, promoted GPR17-dependent guanosine 59-O-(3-[…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…Although multiple follow-up studies consistent with this original report have been published by the same group (Parravicini et al, 2008;Pugliese et al, 2009;Buccioni et al, 2011;Daniele et al, 2011;Coppi et al, 2013), Benned-Jensen and Rosenkilde (2010) reported that UDP and UDP-glucose, but not cysteinyl leukotrienes, promoted GPR17-dependent guanosine 59-O-(3-[…”
Section: Introductionmentioning
confidence: 53%
“…Early characterization of GPR17 mostly focused on (Daniele et al, 2011). However, using the same conditions (cAMP levels elevated by 10 mM forskolin) and the same cells (1321N1), we failed to observe inhibition of cAMP accumulation in over a dozen independent experiments, even though the receptor was expressed at the cell surface based on an intact cell RIA.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recent work has led to the "deorphanization" of the G protein-coupled receptor (GPCR) 5 referred to as GPR17, which is located at an intermediate phylogenetic position between the purinergic P2Y receptors and the CysLT 1 and CysLT 2 receptors for cysteinyl-leukotrienes (cysLTs; [1][2][3][4][5][6]. Both recombinant and native GPR17 receptors respond to uracil nucleotides (e.g.…”
mentioning
confidence: 99%